Microstructural evolution and mechanical property of Ti-6Al-4V wall deposited by continuous plasma arc additive manufacturing without post heat treatment. (May 2017) - Lin, Jianjun; Lv, Yaohui; Liu, Yuxin; Sun, Zhe; Wang, Kaibo; Li, Zhuguo; Wu, Yixiong; Xu, Binshi
Abstract: Plasma arc additive manufacturing (PAM) is a novel additive manufacturing (AM) technology due to its big potential in improving efficiency, convenience and being cost-savings compared to other AM processes of high energy bea\m. In this research, several Ti-6Al-4V thin walls were deposited by optimized weld wire-feed continuous PAM process (CPAM), in which the heat input was gradually decreased layer by layer. The deposited thin wall consisted of various morphologies, which includes epitaxial growth of prior β grains, horizontal layer bands, martensite and basket weave microstructure, that depends on the heat input, multiple thermal cycles and gradual cooling rate in the deposition process. By gradually reducing heat input of each bead and using continuous current in the PAM process, the average yield strength (YS), ultimate tensile strength (UTS) and elongation reach about 877 MPa, 968 MPa and 1.5%, respectively, which exceed the standard level of forging. The mechanical property was strengthened and toughened due to weakening the aspect ratio of prior β grains and separating nano-dispersoids among α lamellar. Furthermore, this research demonstrates that the CPAM process has a potential to manufacture or remanufacture in AM components of metallic biomaterials without post-processing heat treatment. Graphical abstract: Deposited Ti-6Al-4V wall by optimized weld wire-feed continuous plasma arc additive manufacturing process (CPAM) consisted of various morphologies with different microstructure. The evolution of microstructures, including prior β grains, horizontal layer bands, martensite and basket weave microstructure, relate to gradually decrease heat input of layer by layer and multiple thermal cycles. The microstructure of α lamellar with nano-dispersoids significantly improve the mechanical properties without post-processing heat treatments, moreover, the mechanical properties exceed the standard level of forging. Highlights: Aspect ratio of prior β grains are affected by gradually reducing heat input. Horizontal layer bands results from the influence of multiple thermal cycles. α lamellar with nano-dispersoids significantly improves mechanical properties. Different <11–20> poles forming three dominating orientations.